Psychological Profile of Serial Killers: Analysis of Personality Traits, Motivation and Emotional Dynamics - Čekić, Elvira (International Journal of Psychology, 2024)
Purpose: This paper aims to analyze the core emotional and motivational factors influencing serial killers, particularly examining the role of traumatic childhood experiences and psychological disorders in the development of violent tendencies. The study seeks to enhance the understanding of the psychological profiles of serial killers, ultimately providing insights that can inform ethical judicial strategies for identifying and preventing serial homicides. Methodology: A qualitative approach is employed, utilizing psychological, behavioral, and developmental models to comprehensively map the psychological profiles of serial killers. Case studies are examined, emphasizing how early trauma and psychological disorders shape behavior. A comparative analysis investigates key emotional motives and patterns, focusing on the correlation between traumatic experiences and recurrent violent behaviors. Additionally, clinical assessments and available case data are utilized to identify common patterns and individual variations in psychological disorders. Findings: The analysis indicates that a combination of early traumas, psychological disorders, and emotional patterns, such as impulsivity, lack of empathy, and aggression, significantly prevails among serial killers. Traumatic childhood experiences not only shape individual behavior but also play a crucial role in the development of violent tendencies and complex psychological disorders. The interconnection between emotional factors and psychological disorders enables a deeper understanding of the psychological profiles of serial killers, aiding researchers and practitioners in grasping the mechanisms that drive such behavior. The analysis of specific cases reveals a correlation between traumatic experiences and criminal behavior, suggesting that emotional patterns, such as the desire for power and revenge, often reflect internal conflicts or deep-seated trauma. These findings illuminate the complex relationship between emotional dynamics and criminal behavior, providing important insights that can enhance judicial strategies. Understanding these psychological aspects can assist in the development of more effective identification and intervention methods, contributing to an ethical approach in working with individuals who have committed serious crimes. Unique Contributions To Theory, Practice and Policy: This study makes several unique contributions to the fields of psychology and criminology by integrating the understanding of early trauma, psychological disorders, and emotional patterns into the analysis of serial killers' motivations. Theoretically, it expands existing frameworks by emphasizing the interplay of these factors, thereby enriching our comprehension of criminal behavior. In practice, the findings provide valuable insights for law enforcement and mental health professionals, highlighting the importance of a nuanced understanding of the psychological profiles of serial killers. This knowledge can inform more effective investigative techniques and interventions aimed at preventing serial homicides. Policy-wise, the recommendations advocate for the incorporation of these insights into judicial strategies, fostering ethical identification and prevention measures that consider the psychological and sociocultural contexts of serial offenders. By bridging the gap between theory and practice, this study aims to contribute to more informed decision-making processes within the criminal justice system, ultimately enhancing the safety and well-being of communities.